Treat-and-Extend vs. Pro Re Nata Regimen of Ranibizumab for Diabetic Macular Edema—A Two-Year Matched Comparative Study - Lai, Tso-Ting; Chen, Ta-Ching; Yang, Chang-Hao; Yang, Chung-May; Ho, Tzyy-Chang; Hsieh, Yi-Ting (Frontiers in Medicine, 2022)
Purpose To compare 2-year treatment outcomes of ranibizumab using treat-and-extend (T&E) or pro re nata (PRN) regimens for diabetic macular edema (DME) in clinical settings. Methods We retrospectively enrolled 34 patients (34 eyes) with DME treated with ranibizumab using the T&E regimen, and 34 patients (34 eyes) treated with ranibizumab using the PRN regimen and matched to cases in the treat-and-extend group by baseline best-corrected visual acuity (BCVA) and central foveal thickness (CFT). BCVA and CFT changes, number of injections and recurrence of macular edema over 2 years were compared between the groups. Results The average BCVA gain in the T&E and PRN groups was 16.2 and 7.6 ETDRS letters at 2 years (p = 0.011), respectively. The mean CFT reduction was 145.5 ± 127.3 and 97.3 ± 152.5 μm in the T&E and PRN groups at 2 years (p = 0.035), respectively. The T&E group had a higher proportion of patients with BCVA gain ≥ 15 letters at months 18 (p = 0.015) and 24 (p = 0.029) than the PRN group. During the 2-year treatment periods, the T&E group received more injections than the PRN group (11.0 ± 3.2 vs. 6.2 ± 2.0; p < 0.001), while the PRN group had more recurrence of macular edema than the T&E group (71 vs. 41%; p = 0.015). Conclusions After 2-year ranibizumab treatment for DME, better visual and anatomical improvement and less recurrence of macular edema were achieved in the T&E group, with more injections administered.